The traveller from the heavens - Khan, Sr Nafees; Gurmeet (Goodword Books New Delhi, 2007)
"The Traveller from the Heavens" is a mystical and inspiring tale that follows the journey of a divine traveler, exploring themes of spirituality, enlightenment, and the connection between the earthly and celestial realms.